Stress, demographic and life-style factors of non-academic staff with hypertension in Malaysian Public University - Mohamed, Osman Abubakar (2016)
Background: Hypertension is a phenomenon which has been the main cause of high morbidity and mortality rate in both developing and developed countries will continue to prevail if the right action is not taken. the aim was To determine the relationship between the Stress, demographic and lifestyle factors and hypertension among Univeriti Putra Malaysia non-academic staff, aged 25 years old and above. Methodology: Analytical cross-sectional study was conducted after obtaining ethical approval from JKEUPM. Respondents were selected using a simple random sampling with probability proportional to size. The data was collected from October 2014 to January 2015 by using pre-tested self-administered questionnaire and blood pressure measurements. Results: Response rate was 69%. Overall proportion of hypertension among respondents was 8:8%. The proportion hypertension was higher among Females, Malays, Married, Less Educated (Secondary), Less income, supporting staff, moderate duration employment, those with low income, those with positive family history of hypertension and those who were Obese and those who have light physical activity. Result of Chi-Square showed that proportion of hypertension among UPM non-academic staff is lower than prevalence of hypertension among all Universiti Putra Malaysia staff, irrespective cadre. Socio-demographic Factors, Age, Educational Level and Employment Duration were significantly associated with hypertension. Similarly, Body Mass Index was observed to be significantly associated with hypertension. Results of logistic regression showed that the only Predictors of Hypertension in this study was age, Body Mass Index, Physical Indicator. The respondents at the age group 55 years and above have 71 times higher odds of having hypertension compared to those between 25–34 years old (OR = 71:498, 95% CI9:360-546:149, P = 0:0001). Respondents in age group between 45–54 have 21 times higher odds ratio of having hypertension compared to those in age group of 25-34 years OR = 21:198;95% CI(3:756-119:647), p = 0:0001. This association do not have statistical significance. Finally those in age group 35-44years were also found to be about 2 times more likely to have hypertension than those in age group 25-34years, (OR=2.349, 95% CI 0.415-13.288, P=0.334), Meanwhile, odds of having hypertension were observed to be 11 times higher in those with High BMI compared to those with Lower Body Mass Index OR = 10:780;95% CI(4:065–28:588); p < 0:0001. The odds ratio of having hypertension was observed to be 4 times higher among physical Indicator respondents compared to those who were not physical indicator(OR = 4:126;95%CI1:347-12:639;P = 0:013). Conclusion: The study revealed that among all the factors examined, only Age, Body Mass Index, Physical Indicator significantly predicted hypertension. This finding have significant implication on prevention and control of hypertension among non-academic staff in University Putra Malaysia.